A Biodiversidade no meu Recreio: um olhar diferente - Varandas, Ana (2024)
This study emerged as part of the master's degree in Pre-School Education during the Supervised Teaching Practice, specifically in kindergarten, with children aged between 3 and 5 years, and in this study, out of a total of 25 children, only 11 participated. The starting point for this study arose due to the fact that science teaching is an area unexplored by the cooperating educator and the importance of exploring and learning in the outdoor. To this end, a set of activities were carried out in which children were actively involved in their own training by learning, observing, experimenting, reflecting and drawing conclusions about their surroundings. In this way, children better understand the world around them, getting to know it in a more practical and active way. Thus, the following question arose: "What is the impact of hands-on outdoor activities on science learning?" To answer this question, the following objectives were established: know and explore the concept of Biodiversity; understand the diversity of living beings existing in the outdoor; identify different living beings and develop the ability to observe. A qualitative methodology was assumed and an action research integrated in an interpretative paradigm was developed. Direct observation, logbook and informal conversations were used as data collection tools. The results obtained demonstrate that the concepts that were introduced in the group of children were learned in a interested, motivating and playful way, proving that science can be always worked and teached even with small children, regardless their age.